PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP WORK ENGAGEMENT PADA PEGAWAI UPTD PENGELOLAAN JALAN DAN JEMBATAN WILAYAH PELAYANAN VI - Fadillah Syawaliyah; Sunimah Sunimah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the influence of work motivation and job satisfaction on work engagement among employees of the Regional Road and Bridge Management Unit (UPTD) Service Area VI. The background of this study highlights how work-related stress and limited facilities contribute to low work engagement among employees. Using an associative quantitative approach, data were collected via a questionnaire from 110 respondents selected using simple random sampling with the Slovin formula. The results of multiple linear regression analysis ( Y = 9.025 + 0.022 X1 + 0.278 X2) indicate that both work motivation and job satisfaction have a positive and significant influence on work engagement simultaneously, with an F-value of 21.117 (p = 0) However, when analyzed partially, work motivation does not have a positive and significant influence on work engagement ( t = 0.416 , p = 0.678 ) , whereas job satisfaction has a positive and significant influence on work engagement ( t = 4.822 p = 0.000). Specifically, the job satisfaction variable was found to have a more dominant influence (Standardized Beta = 0.504) than work motivation (Standardized Beta = 0.043) in shaping employees' work engagement. This research model accounts for 28.3% of the variance (R2 = 0.283, Adjusted R 2 = 0.27 ) in the work engagement variable, while the remaining 71.7% is influenced by other factors outside the model. These findings confirm that the integration of work motivation and job satisfaction is a key strategy for enhancing civil servants' work engagement in addressing bureaucratic challenges at the local level